Leonardos da Vinci Wende in der Schlacht bei Anghiari: Poetik und genetische Kritik der zeichnerischen Entwürfe - Boesten-Stengel, Albert (Artium Quaestiones, 2020)
In 1505 or 1506, Leonardo da Vinci abandoned his project of the Battle of Anghiari, which was to depict the historical victory in 1440 of Florence over Milan. The last traces of the wall painting were obliterated in the 1560s when Giorgio Vasari and his collaborators restructured and redecorated the once Sala del Maggior Consiglio of the Florentine Republic. More or less contemporary foreign copies seem to reproduce what is believed to be the central part of the composition, known even by the same Vasari’s description as the group of horsemen fighting for a standard, “vn groppo di caualli, che combatteuano vna bandiera”, and only one colour detail, an old soldier in a red cap, “vn soldato vecchio con vn berretton rosso”. Vasari’s words do not identify in the scene any protagonist of the historical event. Only in the eyes of recent interpreters did it become the confrontation of two Milanese horsemen on the left and two Florentine on the right. Observations on Leonardo's method of projecting allow a new approach. The exhibition “Europe in the Renaissance”, organized in 2016 by the Swiss National Museum in Zürich, showed a computer animation produced based on the author’s screenplay by the studio xkopp creative in Berlin. The succession of sequential images demonstrate how both the final composition and the depicted action emerge from Leonardo’s drawing process. The present essay completes the silent animation with the necessarily verbal commentary. The inquiry concerns five original drawing-sheets in the collections of the Gallerie dell'Accademia in Venice and the Szépmüvészeti Múzeum in Budapest. Leonardo calls the first shaping of figures, the rough composition sketch, componimento inculto. From classical poetics he borrows the word, the term, and the priority of suitable actions which the same figures should demonstrate Genetic criticism distinguishes in the simultaneity of unerased strokes the variations of tools and their handling. Arranging the step-by-step changes, first traces, insertions and alternatives in the individual sketch and from sheet to sheet we recognize earlier and later positions and postures of the same protagonists. Just in the first sketch we discern the future “old soldier in a red cap” emerging victorious from the duel. His action represents the causa efficiens of the extreme left horseman’s finally twisted posture. At the beginning of the internal drawing procedure we recognize the same horseman in a different position, how he rides from right to left, holding the staff of the standard like a lance directed to the left. The counterattacking “old soldier”, coming from the left side and evading the mortal thrust, grips the enemy’s standard and turns it in the opposite direction. With few rapid modifications, the draftsman dramatically creates the “reversal” in the battle, Aristotle’s “change from bad fortune to good, or from good fortune to bad” (Poetics, 1451a). The final composition shows the “old soldier” fighting simultaneously at least three enemies like the paradigmatic Hercules defeating the multi-headed Hydra. The victorious “old soldier in the red cap” embodies the Florentine Republic.